INFEKSI MIKORIZA, STATUS HARA, DAN HASIL KERAPATAN TANAMAN TUMPANG SARI JAGUNG KEDELAI YANG DITAMBAHKAN BAHAN ORGANIK - ovie purnawatie (CROP AGRO, Scientific Journal of Agronomy, 2020)
This study was aimed to determine mycorrhizae infection, nutrition status, the yield of maize-soybean intercropping system plant density with mycorrhizae and organic materials addition. The experiment method that been used in this study is the randomized block design with five intercropping system treatment: P1= 2 strips of maize: 2 strips of soybean, P2= 3 strips of maize: 2 strips of soybean, P3= 3 strips of maize: 3 strips of soybean, P4= 4 strips of maize: 2 strips of soybean, P5= 4 strips of maize: 3 strips of soybean. Each treatment was repeated three times to get fifteen trial plots. Based on the result of the study conclusion: (1) soil nutrition content and soil nutrition uptake N, P, and plant C-organic at 40 days after planting and 92 days after planting on the treatment of 3 strips of maize: 3 strips of soybean obtained the highest value from other intercropping treatments, (2) mycorrhizae infection and the amount of spore on maize- soybean at 40 days after planting and 92 days after planting in 3 strips of maize: 3 strips of soybean obtained the highest value from other intercropping treatments, (3) Yield on treatment of 3 strips of maize: 3 strips of soybean get the highest value on mass of corn cobs and soybean pods wet and dry of the plants while the weight of stover, harvested corn cobs and soybean pods wet and dry per plot, 1000 seeds with the highest value compared to other intercropping treatments.